2022
DOI: 10.3390/ijms232415501
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Modulation during Orthodontic Tooth Movement: A Promising Strategy for Novel Diagnostic and Personalized Therapeutic Interventions

Abstract: The Orthodontic Tooth Movement (OTM) is allowed through a mediated cell/tissue mechanism performed by applying a force or a pair of forces on the dental elements, and the tooth movement is a fundamental requirement during any orthodontic treatment. In this regard, it has been widely shown that each orthodontic treatment has a minimum duration required concerning numerous factors (age, patient compliance, type of technique used, etc.). In this regard, the aim of the following revision of the literature is to gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…Stretching deformations in the periodontal ligament and alveolar bone have the ability to stimulate the activation of osteogenic gene expression with the differentiation of osteogenic progenitor cells into mature osteoblasts that deposit osteoid, which subsequently undergoes mineralization. It has been established that bone formation caused by tensile stress is not associated with osteoblast proliferation, but with an increase in the rate of differentiation and maturation of osteoblast progenitor cells [27,31].…”
Section: Resultsmentioning
confidence: 99%
“…Stretching deformations in the periodontal ligament and alveolar bone have the ability to stimulate the activation of osteogenic gene expression with the differentiation of osteogenic progenitor cells into mature osteoblasts that deposit osteoid, which subsequently undergoes mineralization. It has been established that bone formation caused by tensile stress is not associated with osteoblast proliferation, but with an increase in the rate of differentiation and maturation of osteoblast progenitor cells [27,31].…”
Section: Resultsmentioning
confidence: 99%
“…Orthodontic tooth movement is the spatial displacement of teeth caused by the remodelling of the periodontal ligament and alveolar bone through the transfer of tensile force and static pressure to the alveolar bone from the periodontal ligament when a mechanical stimulus force is applied to the teeth. 1,2 Research has shown that the tension and static pressure generated during the orthodontic process increase bone formation on the tension side and bone absorption on the pressure side. 3,4 Periodontal ligament stem cells (PDLSCs) are mesenchymal stem cell/progenitor cells with multipotent differentiation and self-renewal ability in the periodontal ligament.…”
Section: Introductionmentioning
confidence: 99%